Optimization of Customer Segmentation in the Retail Industry Using the K-Medoid Algorithm - Agustin, Endy Wulan; Uthami, Kurnia; Ulfa, Arvan Izzatul; Efrizoni, Lusiana; Rahmaddeni, Rahmaddeni (Institut Riset dan Publikasi Indonesia, 2025)
The retail industry faces significant challenges in understanding increasingly complex customer behavior due to massive data growth. One major obstacle is suboptimal customer segmentation, leading to ineffective marketing strategies. This study aims to optimize customer segmentation by implementing the K-Medoid algorithm, which excels in handling outliers and producing more stable clusters compared to K-Means. The dataset consists of over 10,000 customer transactions from a major retail company in Indonesia. The research process includes data collection and preprocessing, K-Medoid algorithm implementation, and performance evaluation using the silhouette score. The results indicate that the K-Medoid algorithm achieves more accurate customer segmentation, with a silhouette score of 0.39. The generated clusters exhibit greater homogeneity, enabling companies to design more targeted marketing strategies, such as specific discount offers and tailored loyalty programs. Based on these findings, the K-Medoid algorithm is recommended to enhance customer management effectiveness in the retail industry. This study contributes to selecting a more suitable algorithm for customer segmentation in the era of big data and opens opportunities for further exploration of hybrid algorithms and additional evaluation metrics.